Botulinum toxin type A wear-off phenomenon in chronic migraine patients: how long does the maximum efficiency last? - Aygul Tantik PAK; İsmet ÜSTÜN; Yildizhan SENGUL (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Botulinum toxin Type A (BoNTA) is a successful treatment for chronic migraine prophylaxis. Objective: We aimed to evaluate the monthly change of effectiveness of BoNTA treatment. Methods: A total of 80 patients (70 females and 10 males) with chronic migraine were included. In our study protocol, we applied to 155 U across 31 fixed-sites and if the patient had pain, 40 U dose injections were applied across 8 specific head/neck muscle areas. Headache days and analgesic intake were noted before the BoNTA injection and during the interviews at the first, second, and third months after the BoNTA injection. Results: The mean age was 37.59 ± 7.60 and 87.5% of the patients were female. The mean number of headache days/month before BoNTA was 18.95±2.69, decreasing to 10.55±3.15 days/month in the first month (p<0.001), 9.31±2.43 days/month in the second month (p<0.001), and increased to 11.97±3.27 days/month in the third month (p<0.001). The mean analgesic intake before BoNTA was 11.48±4.68 tablets/month, while it decreased to 6.53±2.72 tablets/month in the first month (p<0.001) and 5.40±2.46 tablets/month in the second month (p<0.001). In the third month, it was 5.85±2.59 tablets/month (p<0.001). There was a significant increase in pain medication use from the second to the third month (p<0.001). Conclusion: In our study, there was a significant reduction in analgesic intake and headache days in the first and second months after BoNTA injection, and an increase was observed in the third month.